PERJURY AND WRONGFUL WITNESS TESTIMONY IN CRIMINAL PROCEEDINGS - Dragović, Svjetlana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Execution of evidence using witnesses consists of hearing (examining) witnesses, i.e. taking testimonies from witnesses. Witnesses represent the most commonly used evidence and their testimony, regardless of all shortcomings that follow this evidence, is very important and still irreplaceable evidence in criminal proceedings. The court can only base its decision on true testimony. The witness is obliged to make a true testimony. Giving false testimony (perjury) is a criminal offense. However, certain shortcomings and errors in processes that make a testimony, as well as the way "taking" testimony from witnesses, can lead to perjury. The wrongful testimony is not perjury, nor is the wrongful testimony a criminal offense. In order to make the difference between perjury and wrongful testimony even clearer, the author will first define what is testimony and explain its structure from the judicial-psychological aspect, and then point to the difference between perjury and wrongful witness testimony in criminal proceedings.